Conformational difference between two subunits in flavin mononucleotide binding protein dimers from Desulfovibrio vulgaris (MF): molecular dynamics simulation. (October 2016) - Nunthaboot, Nadtanet; Lugsanangarm, Kiattisak; Pianwanit, Somsak; Kokpol, Sirirat; Tanaka, Fumio; Nakanishi, Takeshi; Kitamura, Masaya
Graphical abstract: Highlights: Structural and dynamical properties of wild-type and mutated E13 K, E13R, E13T, and E13Q of FMN binding protein (FBP) dimers are investigated by means of molecular dynamics simulation (MDS). In crystal structures, subunit A (Sub A) and subunit B (Sub B) were almost completely equivalent in all of the five FBP dimers. However, in solution, structures of the two subunits were not equivalent as predicted by MDS. Water molecules were rarely accessible to Iso in all FBP dimers which are in contrast with other flavoenzymes. Abstract: The structural and dynamical properties of five FMN binding protein (FBP) dimers, WT (wild type), E13 K (Glu13 replaced by Lys), E13 R (Glu13 replaced by Arg), E13 T (Glu13 replaced by Thr) and E13Q (Glu13 replaced by Gln), were investigated using a method of molecular dynamics simulation (MDS). In crystal structures, subunit A (Sub A) and subunit B (Sub B) were almost completely equivalent in all of the five FBP dimers. However, the predicted MDS structures of the two subunits were not equivalent in solution, revealed by the distances and inter-planar angles between isoalloxazine (Iso) and aromatic amino acids (Trp32, Tyr35 and Trp106) as well as the hydrogen bonding pairs between Iso and nearby amino acids. Residue root of mean square fluctuations (RMSF) also displayed considerable differences between Sub A and Sub B and in the five FBP dimers. The dynamics of the whole protein structures were examined with the distance (RNN) between the peptide N atom of the N terminal (Met1) and the peptide N atom of the C terminal (Leu122). Water molecules were rarely accessible to Iso in all FBP dimers which are in contrast with other flavoenzymes.